Cohort-wide deep whole genome sequencing and the allelic architecture of complex traits - Arthur Gilly (Nature Portfolio, 2018)
Rare genetic variants can contribute to complex traits but this contribution is not well understood. Here, the authors analyse deep whole genome sequencing data across 1457 individuals from an isolated Greek population and find association of rare variant burdens with cardiometabolic traits.